2012
DOI: 10.1002/biot.201200110
|View full text |Cite
|
Sign up to set email alerts
|

Systems biology of pathogen‐host interaction: Networks of protein‐protein interaction within pathogens and pathogen‐human interactions in the post‐genomic era

Abstract: Infectious diseases comprise some of the leading causes of death and disability worldwide. Interactions between pathogen and host proteins underlie the process of infection. Improved understanding of pathogen-host molecular interactions will increase our knowledge of the mechanisms involved in infection, and allow novel therapeutic solutions to be devised. Complete genome sequences for a number of pathogenic microorganisms, as well as the human host, has led to the revelation of their protein-protein interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 121 publications
(218 reference statements)
1
22
0
Order By: Relevance
“…As most tick proteins are not annotatable using standard computational tools, the use of in silico method to predict PPIs will may of limited use and we may have to rely on classical techniques such as two‐hybrid, pull down assays, antitag‐mediated co‐immunoprecipitation, peptide arrays, large‐scale co‐immunoprecipitation studies and mass spectrometry to initiate the field. For predicting pathogen–host interactions, in silico methods may prove valuable, as supporting large data sets are available to be used as scaffolds .…”
Section: Insight From Tick Protein Evolution: Targeting Of Binding Spmentioning
confidence: 99%
“…As most tick proteins are not annotatable using standard computational tools, the use of in silico method to predict PPIs will may of limited use and we may have to rely on classical techniques such as two‐hybrid, pull down assays, antitag‐mediated co‐immunoprecipitation, peptide arrays, large‐scale co‐immunoprecipitation studies and mass spectrometry to initiate the field. For predicting pathogen–host interactions, in silico methods may prove valuable, as supporting large data sets are available to be used as scaffolds .…”
Section: Insight From Tick Protein Evolution: Targeting Of Binding Spmentioning
confidence: 99%
“…Although these single-species studies have provided insights into the pathogenic and defensive mechanisms for host-pathogen interactions, they did not give clues about interspecies functional associations between host and pathogen. Detailed knowledge of host-pathogen protein interactions may enable us to comprehend the mechanisms of infection and to identify better strategies to prevent or cure infection [47]. Accordingly, in this study, we developed a computational framework to efficiently construct the interspecies PPI network focusing on the characterization of interspecies interactions between host and pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Even among highly connected proteins (degree k>5) in the human interactome, the degree of virus targets was twice as large as those of nontargeted proteins. Independent analyses found that viral proteins preferably target human host proteins that are involved in a large number of interactions [14,49,50,[54][55][56][57][58][59][60]. As the number of interactions is a local measure of centrality, other more global measures of centrality were considered as well.…”
Section: What Are the Protein Targets Of Human Viruses?mentioning
confidence: 99%
“…Indeed, various viruses target human host proteins with high betweenness centrality. As a corollary, such central proteins also have significantly shorter paths to other proteins [14,49,50,[54][55][56][57][58][59][60], as well as participate in a higher number of pathways and protein complexes [61]. Furthermore, topological analyses of revealed that human host proteins that were targeted by viruses are strongly connected among each other [61].…”
Section: What Are the Protein Targets Of Human Viruses?mentioning
confidence: 99%